The effects of standardized cannabis products in healthy volunteers and patients: a systematic literature review - Leen, Nadia A.; Kowal, Mikael A.; Batalla, Albert; Bossong, Matthijs G. (Frontiers in Pharmacology, 2024)
There is growing recognition of the potential of cannabis to treat various medical conditions and symptoms, such as chronic pain, spasticity, and epilepsy. However, one of the biggest challenges is the assurance of a standardized cannabis product that contains a consistent amount of its main psychoactive substances delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), and which is compliant with predetermined specifications for these compounds. This is crucial not only to ensure consistent cannabis quality and dosage for patients but also to effectively translate research findings into clinical practice. This systematic literature review provides an overview of the effects of standardized cannabis products from Bedrocan, a leading Dutch producer of pharmaceutical-quality standardized medicinal cannabis. Results demonstrate that cannabis administration to healthy volunteers induces dose-dependent acute effects, such as rapidly rising THC and CBD blood concentrations, the subjective experience of high and anxiety, slower reaction time and impaired attention, learning and working memory. Patient studies suggest that treatment with medicinal cannabis reduces pain intensity across a broad range of chronic pain-related medical conditions. Medicinal cannabis showed a mild safety profile, with minor and transient side effects, such as feeling high, coughing and mental confusion. The strength of acute effects, the experience of side effects and the drop-out rate in patient studies may depend on cannabis dose, cannabis composition (CBD:THC ratio), and cannabis use history of participants. Safety and efficacy of standardized medicinal cannabis products should be further investigated in randomized clinical trials with sufficient sample size, with particular focus on cannabis dose and composition, age and differences between males and females.